2017
DOI: 10.2147/ott.s131012
|View full text |Cite
|
Sign up to set email alerts
|

Application of carbon nanoparticles in lymph node dissection and parathyroid protection during thyroid cancer surgeries: a systematic review and meta-analysis

Abstract: PurposeTo investigate whether carbon nanoparticles (CNs) are helpful in identifying lymph nodes and metastatic lymph nodes and in parathyroid protection during thyroid cancer surgery.MethodsEnglish and Chinese literature in PubMed, Cochrane Database of Systematic Reviews, EMBASE, ClinicalTrials.gov, China Biology Medicine Database, China National Knowledge Infrastructure, China Master’s and Doctoral Theses Full-Text Database, Wanfang database, and Cqvip database were searched (till March 22, 2016). Randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 29 publications
3
38
2
Order By: Relevance
“…Since the lymphatic vessels of thyroid gland and parathyroid gland do not communicate with each other, most scholars believe that negative development of parathyroid gland has a protective effect on it, and it has been widely used in thyroid cancer surgery in recent years 9 .The results of this study showed that there was a signi cant statistical difference between the experimental group and the control group in the total number of lymph nodes cleared and the positive rate of metastatic lymph nodes. Consistent with the views of luo wenzheng and other researchers [10][11][12] 11111111111156456466---][i]222115415,Considering carbon nanoparticles can help surgeons better identify lymph nodes in the central region, especially the microscopic nodes that are di cult to be distinguished by the naked eye, reduce lymph node residues, and make it easier and more accurate for pathologists to extract lymph nodes 13 .Together, the two can increase the number of lymph nodes detected, and the corresponding seizure rate of metastatic lymph nodes is also improved, which is conducive to more accurate postoperative judgment of staging and prognosis, as well as elimination of potential sources of lymph node recurrence [14][15] .However, there was no statistical difference in the changes of blood calcium and PTH between the experimental group and the control group at 3 and 30 days after surgery (P > 0. 05), which was consistent with the views of Liu et al [16][17] ] that is, the parathyroid protection is not signi cant.…”
Section: Discusssupporting
confidence: 90%
“…Since the lymphatic vessels of thyroid gland and parathyroid gland do not communicate with each other, most scholars believe that negative development of parathyroid gland has a protective effect on it, and it has been widely used in thyroid cancer surgery in recent years 9 .The results of this study showed that there was a signi cant statistical difference between the experimental group and the control group in the total number of lymph nodes cleared and the positive rate of metastatic lymph nodes. Consistent with the views of luo wenzheng and other researchers [10][11][12] 11111111111156456466---][i]222115415,Considering carbon nanoparticles can help surgeons better identify lymph nodes in the central region, especially the microscopic nodes that are di cult to be distinguished by the naked eye, reduce lymph node residues, and make it easier and more accurate for pathologists to extract lymph nodes 13 .Together, the two can increase the number of lymph nodes detected, and the corresponding seizure rate of metastatic lymph nodes is also improved, which is conducive to more accurate postoperative judgment of staging and prognosis, as well as elimination of potential sources of lymph node recurrence [14][15] .However, there was no statistical difference in the changes of blood calcium and PTH between the experimental group and the control group at 3 and 30 days after surgery (P > 0. 05), which was consistent with the views of Liu et al [16][17] ] that is, the parathyroid protection is not signi cant.…”
Section: Discusssupporting
confidence: 90%
“…Due to the application of carbon nanoparticles as a possible method of unequivocal identification of PGs, the risk of postoperative hypothyroidism is significantly reduced [93][94][95]. Finally, the application of carbon nanoparticles provides more accurate localization of lymph nodes for further dissection during thyroidectomy and better visualization of metastatic lymph nodes [92,[96][97][98][99][100].…”
Section: Carbon Nanoparticles In Parathyroid Glands Localizationmentioning
confidence: 99%
“…In 2016, McWade MA established the clinical utility of autofluorescence spectroscopy for parathyroid detection [20]. In 2017, Wang L reported a metaanalysis, reviewing and supporting the application of carbon nanoparticles in lymph node dissection and parathyroid protection [21]. In 2017, Kim SW applied nearinfrared autofluorescence imaging (NIR) for parathyroid gland detection and showing excellent accuracy rate [22].…”
Section: Discussionmentioning
confidence: 99%